2020
DOI: 10.3390/genes11060627
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics Reveals Gene Families Associated with Predatory Behavior in Photuris femme fatale Fireflies

Abstract: Identifying the basis of phenotypic variation is a key objective of genetics. This work has been mostly limited to model systems with a plethora of genetic manipulation and functional characterization tools. With the development of high-throughput sequencing and new computational tools, it is possible to identify candidate genes related to phenotypic variation in non-model organisms. Fireflies are excellent for studying phenotypic variation because of their diverse and well-characterized behaviors. Most adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…To fully understand the differential expression patterns of olfactory-related genes in various tissues, we mapped the Illumina reads of each RNA sample to the reference transcripts to determine the expression level (McKinley & Lower, 2020). In the above six different annotation methods, a total of 21,833 transcripts were annotated and 11,715 of them were assigned to GO terms.…”
Section: Tissue-specific Expression Analyses By Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully understand the differential expression patterns of olfactory-related genes in various tissues, we mapped the Illumina reads of each RNA sample to the reference transcripts to determine the expression level (McKinley & Lower, 2020). In the above six different annotation methods, a total of 21,833 transcripts were annotated and 11,715 of them were assigned to GO terms.…”
Section: Tissue-specific Expression Analyses By Rna-seqmentioning
confidence: 99%
“…In view of the economic importance of insects in agriculture, forestry, and medicine, various chemosensory genes have been reported in different orders (e.g., De Santis et al, 2006; Li et al, 2015c; Wang et al, 2018). The previous transcriptome analyses also focused on Coleoptera, the largest order of insects (Hunt et al, 2007), yet these were conducted on only a minor number of species, including Tribolium castaneum (Kim et al, 2010; Richards et al, 2008), Dendroctonus ponderosae (Andersson et al, 2019), Anoplophora glabripennis (McKenna et al, 2016), Megacyllene caryae (Mitchell et al, 2012), Brontispa longissima (Bin et al, 2017), Colaphellus bowringi (Li et al, 2015b), Leptinotarsa decemlineata (Schoville et al, 2018), Altica viridicyanea (Xue et al, 2021), Ophraella communa (Ma et al, 2019), Photinus pyralis (McKinley & Lower, 2020), Rhynchophorus palmarum (Gonzalez et al, 2021), Harmonia axyridis (Rondoni et al, 2021), and Batocera horsfieldi (Yang et al, 2018). These beetles belong to Tenebrionidae (Liu et al, 2015a), Cerambycidae, Chrysomelidae (Zhang et al, 2016), Lampyridae, Curculionidae, and Coceinellidae, respectively, but none are members of Cantharidae.…”
Section: Introductionmentioning
confidence: 99%
“…(Ahn et al, 2012; Zhu et al, 2016; Rane et al; 2019), and were widely identified among the transcriptome dataset of Elateroidea (Amaral et al, 2017a; 2017b; 2019b). These genes play fundamental roles in xenobiotic detoxification and degradation of distinct molecules related to an insect diet, detoxification of metabolic compounds, resistance to pesticides, degradation of hormones (Xue et al, 2020), and the degradation of the lucibufagins (defensive steroids), present in some fireflies species and used for defensive purposes (McKinley and Lower, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The gene families are involved with catalytic activity (hydrolase and oxidoreductase activity) and binding (ion, organic cyclic compound, and heterocyclic compound binding), as well as metabolic processes (organic substance, nitrogen, and primary metabolic process), regulatory processes, and response to stimuli (Fig S5A (Amaral et al, 2017a;2017b;2019b). These genes play fundamental roles in xenobiotic detoxification and degradation of distinct molecules related to an insect diet, detoxification of metabolic compounds, resistance to pesticides, degradation of hormones (Xue et al, 2020), and the degradation of the lucibufagins (defensive steroids), present in some fireflies species and used for defensive purposes (McKinley and Lower, 2020).…”
Section: Expansion Of Ortholog Gene Familiesmentioning
confidence: 99%
“…The multiple authors of the Special Issue are among the emerging leaders in this effort, and they share their contributions toward generating a road map connecting the gene networks and phenotypic diversity created by genetic and environmental change. McKinley and Lower [1] describe the unique challenges of and the many opportunities for connecting phenotype and genotype in non-model organisms with their often complex and intriguing behaviors. They use comparative transcriptomics to examine divergent behavior phenotypes in predatory and non-predatory species of fireflies in the genus Photinus.…”
mentioning
confidence: 99%